2004
DOI: 10.1063/1.1647705
|View full text |Cite
|
Sign up to set email alerts
|

Probing the nanoscale electro-optical properties in ferroelectrics

Abstract: We present an approach to inspecting the electro-optical properties of a ferroelectric crystal on the nanometer scale by applying a confined electric field E between a pointed optical fiber and the sample under investigation. Monitoring the optical transmission of barium titanate (BaTiO3) provides a complete image of the ferroelectric domain distribution in a single scan, including also antiparallel domains. The spatial resolution of ∼250 nm in this experiment is determined by the confinement of the electric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] In those applications, it is critical to understand ferroelectric domain orientations and domain switching through external stimulation, where the domain orientations have an intense influence on ferroelectric properties and the fluctuation of domain volume fractions due to domain switching or backswitching dominates the efficiency and stability of ferroelectric devices. [11][12][13][14][15][16][17][18][19][20][21][22][23] Therefore, the precise determination of ferroelectric domain orientations and their volume fractions is required not only in view of ferroelectric device engineering but also in the corresponding physics mechanism, such as fatigue and retention.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In those applications, it is critical to understand ferroelectric domain orientations and domain switching through external stimulation, where the domain orientations have an intense influence on ferroelectric properties and the fluctuation of domain volume fractions due to domain switching or backswitching dominates the efficiency and stability of ferroelectric devices. [11][12][13][14][15][16][17][18][19][20][21][22][23] Therefore, the precise determination of ferroelectric domain orientations and their volume fractions is required not only in view of ferroelectric device engineering but also in the corresponding physics mechanism, such as fatigue and retention.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the symmetry of the optical indicatrix, regions of opposite polarization cannot be distinguished by linear optics. Nonlinear effects, however, such as secondharmonic generation (Dolino, 1973) or the electro-optic effect (Hubert and Levy, 1997;Otto et al, 2004) revealed the eccentricity of the crystal. Regarding materials, lithium niobate (LiNbO 3 ) and lithium tantalate (LiTaO 3 ) emerged as key technological materials for photonic applications (se Fig.…”
Section: Optical Characterizationmentioning
confidence: 99%
“…To date, several optical techniques have been successfully applied for ferroelectric domain characterization and inspection, such as Raman spectroscopy [13,14], electrooptical near-field microscopy [15], defect-luminescence microscopy [16], near-field second-harmonic generation (SHG) * thomas.kaempfe@iapp.de microscopy [17], nonlinear Talbot imaging [18], optical coherence tomography [19], and Cherenkov-type SHG (CSHG) [20]. Although near-field SHG and electro-optical microscopy perform at an ultrahigh resolution beyond the diffraction limit, they constitute scanning probe techniques with a high surface sensitivity but a low penetration depth.…”
mentioning
confidence: 99%